2004
DOI: 10.1038/oby.2004.227
|View full text |Cite
|
Sign up to set email alerts
|

Personality as a Predictor of Weight Loss Maintenance after Surgery for Morbid Obesity

Abstract: LARSEN, JUNILLA K., RINIE GEENEN, CORA MAAS, PIETER DE WIT, TINY VAN ANTWERPEN, NICO BRAND, AND BERT VAN RAMSHORST. Personality as a predictor of weight loss maintenance after surgery for morbid obesity. Obes Res. 2004;12:1828 -1834. Objective: Personality characteristics are assumed to underlie health behaviors and, thus, a variety of health outcomes. Our aim was to examine prospectively whether personality traits predict short-and long-term weight loss after laparoscopic adjustable gastric banding. Research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
3
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 27 publications
1
33
3
6
Order By: Relevance
“…According to the authors, this suggests that personality assessment as intake psychological screening is of little use for the prediction of poor or successful weight outcome after bariatric surgery [25] . Herpertz et al [26] presented a systematic review of psychological and psychosocial variables that could predict weight loss and mental health after bariatric surgery.…”
Section: Surgical and Nonsurgical Treatments: Maintaining The Weight mentioning
confidence: 99%
“…According to the authors, this suggests that personality assessment as intake psychological screening is of little use for the prediction of poor or successful weight outcome after bariatric surgery [25] . Herpertz et al [26] presented a systematic review of psychological and psychosocial variables that could predict weight loss and mental health after bariatric surgery.…”
Section: Surgical and Nonsurgical Treatments: Maintaining The Weight mentioning
confidence: 99%
“…For example, research indicates that economic status, class, mental health difficulties and personality characteristics do not predict postoperative weight loss (Latner et al 2004, Larsen et al 2004 whereas van Hout et al (2005) concluded that younger individuals and those with earlier obesity onset tend to show better outcomes post surgery. Further, Colles et al (2008) found the strongest predictors of weight loss by 12 months following LAGB included a higher baseline BMI, lower rating of subjective hunger, high quality of life related to physical functioning and leisure activities.…”
Section: Introductionmentioning
confidence: 99%
“…Although WLS is still considered the treatment of choice for morbidly obese individuals (NICE; 2009) and is currently one of the most frequently performed procedures in the US and Europe (Nguyen et al 2005), questions have been raised about the long-term durability of weight loss, particularly at 18 -24 months post surgery when research indicates that a substantial proportion of individuals begin to regain lost weight (Bocchieri et al, 2002;Buchwald et al 2004, Larsen et al 2004Sjostrom et al, 2007;Picot et al, 2009). In particular, Herpertz et al (2004) carried out a review of the literature and reported that 30% of patients regain weight post surgery and Magro et al (2008) found that some weight regain was observed in approximately 4 50% of patients (46% within 24 months and 63.6% within 48 months).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to try and achieve weight loss in overweight children, but this is often difficult. Like socioeconomic and psychological factors (9)(10)(11), physiologic factors may also modulate and/or predict the degree of weight reduction. If these factors can be identified, they could be used to individualize and optimize weight-loss programs.…”
Section: Introductionmentioning
confidence: 99%